Wineries and wine quality: The influence of location and archetype in the Hunter Valley region in Australia - Peter Lock; Stuart Mounter; Euan M. Fleming; Jonathan Moss (Wine Economics and Policy, 2019)
Geographical concentrations of wineries often occur within a region for obvious reasons of terroir. However, localised spatial concentrations of wineries may exist because of other factors. This paper explores whether co-location exists among wineries that have higher wine ratings in the Hunter Valley wine region in New South Wales, Australia. Key conclusions are that clustering of Hunter Valley wineries producing high-quality wines does not exist, the quality rating of a winery is influenced by its terroir, and wine quality among wineries in the region is higher for those producing the territorial brand wine of Semillon. Blending was found to have no impact on the quality of wine produced by a winery.
Keywords: 330; Wine quality; Archetypes; Wine cluster; Hunter Valley Australia